Instantaneous wave-free ratio and fractional flow reserve: effect of variation in left ventricular end diastolic pressure. (4th February 2022) - Sharma, P; Vohra, S; Bhandari, M; Sharma, A; Vishwakarma, P; Chaudhary, G; Pradhan, A; Chandra, S; Dwivedi, S K; Sethi, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Among patients with intermediate coronary artery stenosis (50-90%), assessment of functional significance of the lesion by instantaneous wave free ratio (iFR)/ fractional flow reserve (FFR) is recommended in latest guidelines. Though iFR is not much affected by change in hemodynamics compared to FFR, the change in iFR vs FFR due to various hemodynamic factors need a validation. Left ventricular end-diastolic pressure (LVEDP) is one of the hemodynamic factors whose variation and effect on FFR vs iFR is largely unknown. In the present study we evaluated the association of change in LVEDP on the changing pattern of iFR/FFR which may hold a clinical significance especially with percutaneous coronary intervention in heart failure patients. Methods: This was a prospective, investigator-initiated, single-center study involving 20 patients with stable coronary artery disease and at least one intermediate coronary lesion (50-90%). The enrolled patients were subjected to both iFR and FFR along with baseline LVEDP measurement. Subsequently, intravenous nitroglycerine infusion was given to reduce LVEDP and corresponding iFR and FFR were re-evaluated. The dynamic changes in iFR and FFR were studied in relation to changes in LVEDP using Pearson's correlation analysis and linear regression analysis. Results: The mean LVEDP was lowered from 16.20 ± 1.54 mmHg to 9.50 ± 1.10 mmHg, the mean iFR and FFR got changed from 0.80 ± 0.12 to 0.76 ± 0.12 mmHg and 0.75 ± 0.09 to 0.72 ± 0.09 mmHg respectively. On Pearson's correlation analysis, LVEDP change did not show statistically significant correlation (linear relationship) with iFR (p = 0.105, r2 = 0.373) and FFR (p = 0.227, r2 = 0.283) changes across the entire range of stenosis severity and in all vessels. Linear regression analysis did not state any independent correlation between LVEDP and iFR and FFR changes in the study group (p >0.05). The % R2 value for iFR and FFR (as a coefficient of determination) of the regression equation were 13.9% and 8%, which means only these percentages of the total variance in iFR and FFR change were explained by LVEDP changes respectively. There was no serious adverse event related to the procedure. Conclusion: To the best of our knowledge, this is the first study comparing the effect of changes in LVEDP on both iFR and FFR simultaneously. In our study, 1 mmHg change in LVEDP was associated with a change in FFR by 0.004 and change in iFR by 0.004 which didn't reveal any significant association (p = 0.227 and 0.105 respectively). This helps us to put FFR at par with iFR under variable hemodynamics. So either of the variables may be used interchangeably with confidence in varied hemodynamic conditions including patients with heart failure. The correlation was non-significant across entire range of stenosis severity, irrespective of sex, age, diabetes and hypertension. This study sets platform for further research with larger number of heterogeneous patient population.